Effect of dexamethasone versus dexamethasone with granisetron in prevention of nausea and vomiting in caesarian section under spinal anesthesia: a randomized double blind study - Das, Mahashweta; Binarani, Maharabam; Anita Devi, Ningthoujam; Meitei, Ashen Jack; Deb Nath, Malin; Devi, L. Eshori (International Journal of Research in Medical Sciences, 2025)
Background: Postoperative nausea and vomiting (PONV) are a common occurrence in patients undergoing caesarean section under spinal anaesthesia. It can lead to adverse events like pain, bleeding, dehydration, electrolyte imbalance, aspiration pneumonia etc. Methods: This study was aimed at comparing the effectiveness of dexamethasone alone with dexamethasone with granisetron in prevention of PONV in patients undergoing caesarean section under spinal anaesthesia. This was a double blinded prospective randomized controlled trial conducted on 60 pregnant mothers undergoing elective caesarean section under spinal anaesthesia. One group of patients (n=30) received dexamethasone 8 mg intravenously whereas the other group received dexamethasone 8 mg plus granisetron 2 mg intravenously after baby was delivered and cord clamped. Patients were then observed for a period of 24 hrs postoperatively. Results: Upon comparison of PONV score between both groups, at 0-2 hrs dexamethasone-granisetron (PONV 0=50%, 1=33.3%, 2=13.3%, 3=3.3%) showed better control than dexamethasone alone (PONV 0=40%, 1=36.7%, 2=16.7%, 3=6.7%). Similar results were seen at 2-24 hrs with dexamethasone-granisetron (PONV 0=83.3%, 1=16.7%, 2=0%, 3=0%) having better score than dexamethasone (PONV 0=66.7%, 1=26.7%, 2=3.3%, 3=3.3%). Need for rescue antiemetic was less in dexamethasone+granisetron (5 out of 30=16.7%) compared to dexamethasone (10 out of 30=33.3%). No major side effects were seen. Conclusions: Our study shows that dexamethasone combined with granisetron is a safe and effective prophylactic antiemetic in pregnant ladies undergoing caesarean section under spinal anaesthesia, compared to monotherapy of dexamethasone.